Cerebral Abscess – Sequel of Septic Embolization from Thrombo- Phlebitis at Venous Catheter Insertion Site - Mosharraf, Shafayat Bin Mollah; Rahman, Shamimur (Journal of Enam Medical College, 2018)
Abstract not available J Enam Med Col 2018; 8(3): 177-178